Improved accuracy of ratio multiple valuation - Saputro, Julianto Agung; Hartono, Jogiyanto (EDP Sciences, 2017)
Multiple valuation is widely used by investors and practitioners but its accuracy is questionable. Multiple valuation inaccuracies are due to unreliability of information used in valuation, inaccuracies comparison group selection, and use of individual multiple values.This study investigated the accuracy of valuation to examine factors that can increase the accuracy of the valuation of multiple ratios, that are discretionary accruals, the comparison group, and the composite of multiple valuation. These results indicate that multiple value adjustment method with discretionary accruals provides better accuracy, the industry comparator group method combined with the size and growth of companies also provide better accuracy.Composite of individual multiple valuation gives the best accuracy.If all of these factors combined, the accuracy of valuation of multiple ratios will give the best results.